Determinants of financial reporting fraud intention among accounting practitioners in the banking sector: Malaysian evidence - Awang, Yunita; Ismail, Suhaiza (Emerald, 2018)
Purpose: This study attempts to examine the influence of attitude, subjective norm and ethical judgment on unethical financial reporting intention among Malaysian accounting practitioners in the banking industry. Design/methodology/approach: In achieving the objective, questionnaire survey was used. With 121 samples of participants in the financial reporting process, data analysis was conducted using partial least square structural equation modelling (PLS-SEM). Findings: The results indicate that attitude, subjective norm and ethical judgment are significant in influencing unethical financial reporting intention, with ethical judgment having the smallest effect on such intention. Practical implications: Findings of this study are useful in guiding management and regulators to develop strategies to curb the occurrence of unethical financial reporting. This study also gives some insights to the public, especially the banks’ shareholders and depositors into the unethical financial reporting intention of actual participants in the financial reporting process, who are being entrusted to handle the reporting affairs of banking institutions. Originality/value: This study is the first to examine the factors influencing accounting practitioners’ intention to financial reporting fraud in a Malaysian banking setting. As it examines the actual participants in the financial reporting process, the results contribute towards a better understanding on unethical financial reporting intention within banking institutions as highly regulated industry. Additionally, it provides evidence for the suitability of the PLS-SEM in statistical analysis.